Task‐specific strength increases after lower‐limb compound resistance training occurred in the absence of corticospinal changes in vastus lateralis. Issue 7 (22nd May 2020) - Ansdell, Paul; Brownstein, Callum G.; Škarabot, Jakob; Angius, Luca; Kidgell, Dawson; Frazer, Ashlyn; Hicks, Kirsty M.; Durbaba, Rade; Howatson, Glyn; Goodall, Stuart; Thomas, Kevin
Abstract : New Findings: What is the central question of the study? Are corticospinal responses to acute and short‐term squat resistance training task‐specific? What is the main finding and its importance? A single bout of resistance training increased spinal excitability, but no changes in corticospinal responses were noted following 4 weeks of squat training despite task‐specific increases in strength. The present data suggest that processes along the corticospinal pathway of the knee extensors play a limited role in the task‐specific increase in strength following resistance training. Abstract: Neural adaptations subserving strength increases have been shown to be task‐specific, but responses and adaptation to lower‐limb compound exercises such as the squat are commonly assessed in a single‐limb isometric task. This two‐part study assessed neuromuscular responses to an acute bout (Study A) and 4 weeks (Study B) of squat resistance training at 80% of one‐repetition‐maximum, with measures taken during a task‐specific isometric squat (IS) and non‐specific isometric knee extension (KE). Eighteen healthy volunteers (25 ± 5 years) were randomised into either a training ( n = 10) or a control ( n = 8) group. Neural responses were evoked at the intracortical, corticospinal and spinal levels, and muscle thickness was assessed using ultrasound. The results of Study A showed that the acute bout of squat resistance training decreased maximum voluntary contraction (MVC) for up to 45 min post‐exercise (−23%, P < 0.001). From 15–45 min post‐exercise, spinally evoked responses were increased in both tasks ( P = 0.008); however, no other evoked responses were affected ( P ≥ 0.240). Study B demonstrated that following short‐term resistance training, participants improved their one repetition maximum squat (+35%, P < 0.001), which was reflected by a task‐specific increase in IS MVC (+49%, P = 0.001), but not KE (+1%, P = 0.882). However, no training‐induced changes were observed in muscle thickness ( P = 0.468) or any evoked responses ( P = 0.141). Adjustments in spinal motoneuronal excitability are evident after acute resistance training. After a period of short‐term training, there were no changes in the responses to central nervous system stimulation, which suggests that alterations in corticospinal properties of the vastus lateralis might not contribute to increases in strength. Abstract :